TEACHING ENGLISH VOCABULARY IN THE THEME FRUITS AND ANIMALS BY USING SNOWBALL THROWING TECHNIQUE (STT) TO THE SEVENTH GRADERS - Heru Setiawan (Jurnal Didascein Bahasa, 2017)
ABSTRACT: The problem of this study was: ”Is it effective to teach vocabulary by using STT to the seventh grade students of Karya Ibu Junior High School of Palembang?”.Therefore the objective of this study was to find out whether or not it was effective to teach vocabulary to the seventh grade students of Karya Ibu Junior High School of Palembang by using STT. The population of the study was all the seventh grade students of Karya Ibu Junior High School of Palembang in academic year of 2015/2016 with total member of 230. Its sample was taken from class VII. 5 which consisted of 37 students. The method was pre experimental design. In collecting the data, the researcher gave written test in the form 40 multiple choices, and in analyzing the data used match t-test. It was found that teaching English vocabulary by using snowball throwing was effective. It could be seen from the means difference between the result of the pre-test and the result of the post-test. The average of the students’ score in the pre-test was 7.5 and the average of the students’ score in the post-test was 9.25. There was a significantly different score between the result of the t-obtained and t-table. In this study, the result of the t-obtained was 2.154 and t-table was 1.697. It could be concluded that it was effective to teach English vocabulary by using STT to the seventh grade students of Karya Ibu Junior High School of Palembang.Key words: teaching, vocabulary, STT